Assessment of biosurfactant-producing bacteria from enriched shola forest soil and its oil degradation potential - Selvakumar, Kasthuri; Alagirisamy, Bharani; Eswaran, Kokiladevi; Doraiswamy, Uma; Subhashini, R; Thangavel, Kalaiselvi (Plant Science Today, 2026)
This study engineered a highly synergistic bacterial consortium for enhanced bioremediation of marine oil spills. The consortium was designed from 5 distinct biosurfactant-producing strains, isolated from a novel niche: shola forest rhizosphere soil enriched with petroleum-contaminated sediments and cocopeat. Through systematic screening under marine-relevant conditions such as pH, temperature and moisture stress induced by NaCl and PEG 6000, 5 strains were identified with exceptional halotolerance and hydrocarbon-degrading functions. Among isolates, Ochrobactrum tritici demonstrated direct hydrocarbon adhesion via 82 % cell surface hydrophobicity and a Rhizobium sp., a potent emulsifier, maintaining 76 % emulsification index (E24) even at 3 % NaCl. The consortium, comprised of 5 strains, exhibited strong synergistic interactions, achieving an exceptional 94 % degradation of 5 % (v/v) crude oil under standard laboratory conditions. Under simulated marine stress conditions, it maintained a high degradation efficiency of 88 %, outperforming individual strains by 1.5 to 2.5-fold. This work provides a marine-adapted, functionally synergistic microbial strategy for effective oil remediation in challenging coastal and ocean environments.